Efficacy and safety of traditional Chinese medicine in the treatment of chronic pulmonary diseases: a systematic review and meta-analysis - An, Shan; Cai, Hong-Yan (Frontiers in Medicine, 2025)
BackgroundTo assess the efficacy and safety of various TCMIs treatments for COPD using network meta-analysis, providing evidence and guidance for clinical practice.MethodsWe will search 7 databases for randomized controlled trials of TCMI for the COPD, including PubMed, the Cochrane Library, EMbase, China National Knowledge Infrastructure, China Biological Medicine, Chinese Scientific Journals Database, and Wan-fang databases, from the date of the establishment of each database to October 31, 2021. The network meta-analysis will be implemented through Aggregate Data Drug Information System 1.16.8 and Stata13.0 software. Pulmonary function included forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and FEV1/FVC will be the primary outcomes, FEV1 as a percentage of the estimated value, maximal voluntary ventilation (MVV), MVV as a percentage of the estimated value, 6 min walking distance, The St.ResultsA total of seven appropriate studies were identified, encompassing 490 patients. The quality of the literature was satisfactory, with no significant publication bias detected. The effectiveness rate for patients receiving a combination of TCM and Western Medicine (WM) compared to those on WM alone was evaluated as an odds ratio (OR), with statistical testing yielding Z = 6.09. For PO2 levels post-treatment, the mean difference (MD) was reported as 5.92.ConclusionThe results of this study will evaluate the efficacy and safety of TCMI in the treatment of COPD, and provide decision-making references for future clinical and scientific research.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251047046, identifier CRD420251047046.